Fyn and ZAP-70 are required for Vav phosphorylation in T cells stimulated by antigen-presenting cells. - Michel, F; Grimaud, L; Tuosto, L; Acuto, O (1998)
In T cells, triggering of the T cell antigen receptor or of the co-stimulatory receptor CD28 can direct tyrosine phosphorylation of the signaling protein Vav. We investigated the role played by the protein tyrosine kinases Fyn, Lck, and ZAP-70 in these processes in a T cell hybridoma after physiological stimulation of the T cell receptor (TCR) and CD28. A dominant-negative mutant approach based on overexpression of catalytically inactive alleles of these kinases showed that CD28-induced Vav phosphorylation preferentially requires Fyn, whereas ZAP-70 had no role. Consistently, Vav was strongly phosphorylated in Lck-deficient JCAM-1 cells after CD28 ligation. In contrast, ZAP-70 appeared to control TCR-directed Vav phosphorylation. However, overexpression of ZAP-70 carrying a mutated Tyr315, contained within a motif previously suggested to be a Vav Src homology 2 domain binding site, had little or no effect. Immunoprecipitation assays showed that phosphorylated Vav associated with Fyn after CD28 triggering and that this interaction, likely to involve binding of Fyn Src homology 2 domain to Vav, was more strongly detectable after concomitant CD28 and TCR stimulation. These data suggest that Fyn plays a major role in controlling Vav phosphorylation upon T cell activation and that the mechanism implicating ZAP-70 in this process may be more complex than previously anticipated.